Lista de insectos daninos y beneficos recolectados en cultivo de yuca 1973-1976 - Pena, J. (International Center for Tropical Agriculture, 1977)
A list is given of harmful and beneficial insects found on cassava in several localities of the states of Valle del Cauca, Huila and Santander and the Llanos Orientales (Colombia) from 1973- 1976. Data include the insect order, family and species, as well as the type of damage caused. (CIAT)